A new species of Dendrelaphis (Serpentes: Colubridae) from Southeast Asia - Vogel, Gernot; van Rooijen, Johan (Zootaxa, 2007)
A new species of the colubrid genus Dendrelaphis Boulenger 1890 is described. Dendrelaphis kopsteini sp. nov. ranges from Thailand through Peninsular Malaysia and Singapore to Sumatra. A detailed statistical analysis of the differences between D. kopsteini sp. nov., D. formosus (Boie, 1827) and D. cyanochloris (Wall, 1921) is provided as the three species have been mixed up frequently in the literature. D. kopsteini sp. nov. differs from all other Dendrelaphis species by a brick red neck coloration. A neotype is designated and described for D. formosus and a lectotype is designated and described for D. cyanochloris.